(3GdehGQO hJfejJgG (B:s (3CSS hJWHjbGJ Ydi GdhWf GdYQHj (B/s - (3UGdM, MSf YHO GdbGOQs ((3YeGf(B: s (3OGQ hGFd ddfTQ(B, s, 2002)
(3ebOeI GdOQGSI hefgLgG,eaghegG hJUfjagG hGdYdGbGJ GdbGFeI ajeG HjfgG,GdfXGe GdEbJUGOj aj GdhWf GdYQHj,GdehGQO GdWHjYjI aj GdhWf GdYQHj,GdehGQO GdRQGYjI hGdZPGFjI aj GdhWf GdYQHj,GdehGQO GdUfGYjI hGdWGbI aj GdhWf GdYQHj,GdNOeGJ aj GdhWf GdYQHj,GdehGQO GdHTQjI aj GdhWf GdYQHjs
(3HHdhZQGajG(B: (3U(B.372(3;agQS GdCTcGd U(B.393 (3agQS GdLOGhd U(B.391s
Keywords: (3GdCbdjGJs; (3GdehGQO GdWHjYjIs; (3GdfXe GdGbJUGOjIs; (3JfejI GdGbJUGOjIs